Effects of Interactive Educational Videos on Learning Interest and Social Studies Achievement in Elementary School: A Quasi-Experimental Study - Dara Zuknilarinta; alfroki martha; weni yulastri (Journal of Education Research, 2026)
The integration of digital media in elementary education has gained increasing attention, yet empirical evidence on the specific effects of educational video on student interest and learning outcomes in Social Studies remains limited. This study aimed to examine the effect of educational video media use on learning interest and Social Studies learning outcomes among fourth-grade students at SD Negeri 67/III Lubuk Paku. A quasi-experimental design with a non-equivalent control group was employed, involving 40 students divided into experimental and control groups of 20 each. Data were collected through pre-tests, post-tests, and a learning interest questionnaire, and analyzed using descriptive statistics, independent-samples t-tests, and descriptive categorical analysis of learning interest scores. Results indicated that students in the experimental group achieved a significantly higher mean post-test score (82.50) than those in the control group (68.15), with a statistically significant difference (t = 5.847, p = 0.000, less than 0.001). Learning interest in the experimental group was categorized as very high (mean score 78.40 out of 80; 97.5%), as measured using a four-point Likert questionnaire and analyzed using a descriptive-categorical classification. These findings confirm that educational video media effectively enhances both student interest and Social Studies achievement in the rural elementary classroom context, and suggest that its integration into regular IPS instruction represents a practically viable and theoretically grounded strategy for improving learning quality in resource-constrained Indonesian schools.